RFC1 AAGGG repeat expansion masquerading as Chronic Idiopathic Axonal Polyneuropathy - Tagliapietra, Matteo; Cardellini, Davide; Ferrarini, Moreno; Testi, Silvia; Ferrari, Sergio; Monaco, Salvatore; Cavallaro, Tiziana; Fabrizi, Gian Maria (Journal of neurology, 2021)
Background A biallelic intronic AAGGG repeat expansion in the Replication Factor C subunit 1 ( RFC1 ) gene has been recently associated with Cerebellar Ataxia, Neuropathy, Vestibular Areflexia Syndrome, a disorder often presenting as a slowly evolving sensory neuropathy at the onset. “Chronic Idiopathic Axonal Polyneuropathy” (CIAP) is a common indolent axonal neuropathy of adulthood which remains without an identifiable cause despite thorough investigations. Methods We screened 234 probands diagnosed with CIAP for a pathogenic biallelic RFC1 AAGGG repeat expansion. Patients were selected from 594 consecutive patients with neuropathy referred to our tertiary-care center for a sural nerve biopsy over 10 years. Results The RFC1 AAGGG repeat expansion was common in patients with pure sensory neuropathy (21/40, 53%) and less frequent in cases with predominantly sensory (10/56, 18%, P < 0.001) or sensorimotor (3/138, 2%, P < 0.001) neuropathy. The mutation was associated with sensory ataxia ( τ b = 0.254, P < 0.001), autonomic disturbances (35% vs 8%, Prevalence Odds Ratio—POR 6.73 CI 95% 2.79–16.2, P < 0.001), retained deep tendon reflexes (score 18.0/24 vs 11.5/24, R = 0.275, P < 0.001). On pathology, we observed absent/scant regenerative changes ( τ b = − 0.362, P < 0.001), concomitant involvement of large (100% and 99%, n.s.), small myelinated (97% vs 81%, POR 7.74 CI 95% 1.03–58.4, P = 0.02) and unmyelinated nerve fibers (85% vs 41%, POR 8.52 CI 95% 3.17–22.9, P < 0.001). Cerebellar or vestibular involvement was similarly rare in the two groups. Conclusions This study highlights the frequent occurrence of the RFC1 AAGGG repeat expansion in patients diagnosed with CIAP and characterizes the clinical and pathological features of the related neuro(no)pathy.